2010
DOI: 10.1007/s00044-010-9412-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation and docking studies of flavone derivatives on aldose reductase involved in diabetic retinopathy, neuropathy, and nephropathy

Abstract: The enzyme aldoreductase which plays an important role in pathogenesis of diabetic retinopathy, neuropathy, and nephropathy was purified from bovine lens, and its inhibitory activity was studied with the synthesized flavone derivatives 1-(2-hydroxyphenyl)ethanone as the starting material. Experimental study revealed that 2-chloroflavone shows less inhibitory activity of 60-70% than other flavones used in the study. To validate experimental results computationally, docking studies of new flavone derivatives syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Additionally, there was an upregulation of inflammatory genes including Mtor, Tgfb1, and tnf. These findings align with our earlier hypotheses and support the proposed pathway involving the role of adiponectin [98][99][100] Future Directions and Challenges: A multimodal strategy is required for future developments in adiponectin-based diabetic therapy. Adiponectin receptor agonists are being developed by researchers in order to imitate the positive effects of adiponectin on insulin sensitivity and glucose metabolism.…”
Section: Single Cell Data From Db/db Mice Pancreatic Islet Cellssupporting
confidence: 89%
“…Additionally, there was an upregulation of inflammatory genes including Mtor, Tgfb1, and tnf. These findings align with our earlier hypotheses and support the proposed pathway involving the role of adiponectin [98][99][100] Future Directions and Challenges: A multimodal strategy is required for future developments in adiponectin-based diabetic therapy. Adiponectin receptor agonists are being developed by researchers in order to imitate the positive effects of adiponectin on insulin sensitivity and glucose metabolism.…”
Section: Single Cell Data From Db/db Mice Pancreatic Islet Cellssupporting
confidence: 89%
“…One such important repair enzyme is poly (ADP-ribose) polymerase 1 (PARP1) [4] [5]. Several PARP1 inhibitors like nicotinamide, benzamide, 3-amino benzamide (3AB), 9-phenylacridine (ACPH), NU1025, NU1088, PD128763 are often used in conjunction with cisplatin to make it effective at low doses [5]. Several avones are also known to have PARP1 inhibitory activities [6], among them a synthetic avone derivative is 2-(4-Nitrophenyl)-4H-chromen-4-one (4NCO).…”
Section: Introductionmentioning
confidence: 99%
“…From our earlier work based on in silico studies, we have observed that 4NCO could bind at the catalytic site of PARP1 thereby acting as a potent competitive inhibitor hindering the entry of nicotinamide adenine dinucleotide (NAD + ), the natural substrate of PARP1 [7]. 4NCO is a biologically potent avone derivative that also possesses anti-in ammatory, anxiolytic, antioxidant, antitumor and anti-metastatic activities and also known for its tyrosine kinase, BDZ receptor, CDK2, CK2, aldose reductase and DNA binding properties [8] [9][10] [11] [12]. In this work, we have therefore investigated the possible synergism between 4NCO and cisplatin in cancer cells.…”
Section: Introductionmentioning
confidence: 99%